Impact Analysis Of Monetary And Fiscal Policies On Indonesia’s Economic Growth - Rachmawaty Rachmawaty; Bulan Oktrima; Waluyo Jati (Jurnal Manajemen, 2024)
After the Covid-19 pandemic, the world faced economic challenges stagflation, namely high inflation and declining economic growth. To overcome this, the Government made arrangements through monetary and fiscal policies. This study analyses the effect of monetary and fiscal policies on Indonesia's economic growth. This research has eight obtained monetary, fiscal and other macro-economic variables, a novelty compared to the previous researcher. Based on the impulse response analysis in the Vector Error Correction Model, the highest impacted variables to maintain economic growth were the growth of income tax and capital market index, and to negatively impact were exchange money and government expenditure. Over an extended period, it shows that the increase in inflation, money exchange, number of broad-money, interest rate, and government expenditure will impact the decrease of economic growth. In contrast, the increase in government income from tax and capital market indexes will impact the increase in economic growth.